2018
DOI: 10.1016/j.nmd.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene panel screening is an effective tool to identify undiagnosed late onset Pompe disease

Abstract: Mutations in the GAA gene may cause a late onset Pompe disease presenting with proximal weakness without the characteristic muscle pathology, and therefore a test for GAA activity is the first tier analysis in all undiagnosed patients with hyperCKemia and/or limb-girdle muscular weakness. By using MotorPlex, a targeted gene panel for next generation sequencing, we analyzed GAA and other muscle disease-genes in a large cohort of undiagnosed patients with suspected inherited skeletal muscle disorders (n = 504). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…LGMD [31,36,63,64]. The current study has now illustrated the effectiveness of NGS with the largest patient sample from a Latin American population.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…LGMD [31,36,63,64]. The current study has now illustrated the effectiveness of NGS with the largest patient sample from a Latin American population.…”
Section: Discussionmentioning
confidence: 66%
“…Over 8 years of data with over 1200 patients from approximately 220 families in North America, Europe, and Asia have demonstrated that NGS is an effective strategy for improving the diagnosis of patients with proximal muscle weakness [3,5,33,36, and identifying patients with Pompe disease among those with unclassified…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased prevalence (2.4-3.63%) in LOPD was observed previously in LGMD-suspected or hyperCKemia patients using targeted sequencing approach. [46][47][48] But these studies are different with regard to much lower number of patient cohort that unlike our study also included non-LGMD other NMD patients such as other congenital myopathies, distal myopathies, and isolated hyperCKemia in European population. Our results of prevalence of LOPD through targeted LGMD gene-panel testing in a very large strictly clinically LGMD-characterized or -suspected patients across US with multiple ethnicities indicate that LOPD should not be overlooked when considering potential diagnoses for LGMD patients even if clinical subtyping can be performed, that in turn will assist in ERT or recruitment for other clinical trials.…”
Section: Discussionmentioning
confidence: 93%
“…The resulting lower costs and better technological improvements will make NGS approaches an effective first-tier screening method in the near future 62. At present, the gold standard for the LOPD screening tool is the DBS test, which is reliable, fast, cost-effective and easily accessible.…”
Section: Discussionmentioning
confidence: 99%